2020
DOI: 10.3390/cryst10010050
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Doped Lithium Tantalate Thin Films Deposited by Magnetron Sputtering: A Study of the Iron Role in the Structure and the Derived Magnetic Properties

Abstract: Fe-doped LiTaO3 thin films with a low and high Fe concentration (labeled as LTO:Fe-LC and LTO:Fe-HC, respectively) were deposited by magnetron sputtering from two home-made targets. The dopant directly influenced the crystalline structure of the LiTaO3 thin films, causing the contraction of the unit cell, which was related to the incorporation of Fe3+ ions into the LiTaO3 structure, which occupied Li positions. This substitution was corroborated by Raman spectroscopy, where the bands associated with Li-O bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…As seen in Figure S5B, new Raman bands appeared at 830 cm –1 , indicative of broken symmetry of the BO 6 octahedra in an ideal cubic perovskite ABO 3 . The occupation of the Na site by a La 3+ cation is supposed to be sufficient to breakdown the fully symmetric breathing vibrations (A 1g ) of the TaO 6 octahedra. In fact, LiTaO 3 with large distortion (Ta–O–Ta angle of 143°) due to the considerably small A site cation provides a Raman peak at 860 cm –1 . , …”
Section: Results and Discussionmentioning
confidence: 99%
“…As seen in Figure S5B, new Raman bands appeared at 830 cm –1 , indicative of broken symmetry of the BO 6 octahedra in an ideal cubic perovskite ABO 3 . The occupation of the Na site by a La 3+ cation is supposed to be sufficient to breakdown the fully symmetric breathing vibrations (A 1g ) of the TaO 6 octahedra. In fact, LiTaO 3 with large distortion (Ta–O–Ta angle of 143°) due to the considerably small A site cation provides a Raman peak at 860 cm –1 . , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Except the weak mode centered at ∼754 cm −1 which may be a second-order Raman mode or due to trace impurity, all other 11 modes were observed before. Previous experimental and theoretical studies [14][15][16] have determined that the modes above 500 cm −1 correspond to Ta-O stretching and the three bands with lowest frequencies are mainly assigned to the deformation of Ta-O framework. The modes between 270-400 cm −1 are relative to Li-O stretching, which has been obvious influenced by Li displacement in LiNbO 3 [23].…”
Section: (B)) the Maximum Strain Generated Bymentioning
confidence: 95%
“…These perovskites have been extensively investigated over the past few decades because of various applications in nonlinear optics, electro-optics and acousto-optic devices [2][3][4][5][6][7][8][9][10]. Previous experiments have revealed that a small defect concentration [11,12] or doping [13,14] drastically change the physical properties. Raman spectroscopy is very sensitive to small chemical or structural modification of the compounds and has been widely used for the study of these ferroelectric materials [11,15,16]; however, the full assignment of the phonon modes remain under discussion [15,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the search for new magnetic materials, some non-magnetic ABO 3 -type oxides doped with 3d magnetic cations have attracted much attention due to the possibility of inducing ferromagnetism in them, expanding this way the range of technological applications. Nowadays, there are reports already of systems such as LN:Mn, LN:Fe, LiTaO 3 (LT):Fe, BaTiO 3 :Fe, and SrTiO 3 :Co that exhibit ferromagnetism at room temperature (RT) [187][188][189][190][191][192].…”
Section: Dilute Magnetic Oxides and Ferromagnetism In Linbo 3 Doped With Magnetic 3d Cationsmentioning
confidence: 99%